Peran Media Sosial YouTube dalam Meningkatkan Motivasi Belajar - Aulia, Finasti; Rahmanita, Rahmanita; Basri, Muh. Bahly (Nuances of Indonesian Language, 2025)
YouTube as a popular social media platform, has the potential to increase student motivation through interactive and visual learning content. This research aims to explore more deeply how the utilization of YouTube can increase the learning motivation of Makassar State University students. The type of research used in this study is a case study with a qualitative approach. Data collection uses a list of questions in the form of a questionnaire distributed to students of Makassar State University. The data analysis techniques used are descriptive, interpretative, and contextual. The results showed that YouTube is effective in increasing students' learning motivation through interesting educational content. Internal factors such as health and psychology, as well as external factors such as social support and internet access, influence its success as a learning medium. Through optimal use, YouTube can be a useful learning support tool.